Beyond tradition: exploring the non-canonical functions of telomeres in meiosis - Fernández-Álvarez, Alfonso (Frontiers in Cell and Developmental Biology, 2023)
The telomere bouquet is a specific chromosomal configuration that forms during meiosis at the zygotene stage, when telomeres cluster together at the nuclear envelope. This clustering allows cytoskeleton-induced movements to be transmitted to the chromosomes, thereby facilitating homologous chromosome search and pairing. However, loss of the bouquet results in more severe meiotic defects than can be attributed solely to recombination problems, suggesting that the bouquet’s full function remains elusive. Despite its transient nature and the challenges in performing in vivo analyses, information is emerging that points to a remarkable suite of non-canonical functions carried out by the bouquet. Here, we describe how new approaches in quantitative cell biology can contribute to establishing the molecular basis of the full function and plasticity of the bouquet, and thus generate a comprehensive picture of the telomeric control of meiosis.